Changes in Perceived Exertion, Well-Being, and Recovery During Specific Judo Training: Impact of Training Period and Exercise Modality - Ouergui, Ibrahim; Ardigò, Luca Paolo; Selmi, Okba; Levitt, Danielle Evé; Chtourou, Hamdi; Bouassida, Anissa; Bouhlel, Ezdine; Franchini, Emerson (Frontiers in Physiology, 2020)
The present study investigated the effect of intense and tapering training periods using different exercise modalities (i.e., Randori - grip dispute practice without throwing technique, Uchi-komi - technique repetition training, and sprinting) on rating of perceived exertion (RPE), well-being indices, recovery state, and physical enjoyment in judo athletes. Sixty-one adolescent male and female judo athletes (age: 15±1 years) were randomly assigned to one of three experimental or one control groups. Experimental groups (Randori, Uchi-komi, and running) trained 4 times per week for 4 weeks of intense training (in addition to their usual technical-tactical judo training; control group underwent only such a training) followed by 12 days of tapering. RPE, well-being indices (i.e., sleep, stress, fatigue, and delayed onset muscle soreness [DOMS]), total quality of recovery (TQR), and physical enjoyment were measured every session. RPE, sleep, stress, fatigue, DOMS, Hooper index (HI; sum of wellbeing indices), and TQR were lower in the tapering compared with the intensified training period (P<0.001). Moreover, the running group showed better values for sleep (P<0.001), stress (P<0.001), fatigue (P=0.006), DOMS (P<0.001), and HI (P<0.001) in comparison with the other training groups, indicating a more negative state of wellbeing. The Randori and Uchi-komi groups showed higher values for TQR and physical enjoyment (both P<0.001) than the running group, whereas RPE was lower in the control compared with all training groups (P<0.001). Coaches should use more specific training modalities (i.e., Randori and Uchi-komi) during intensified training and should monitor well-being indices, RPE, and TQR during training periods. Moreover, for all variables, 12 days tapering period are beneficial for improving wellbeing and recovery after four weeks of intense training.